ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK PERKREDITAN RAKYAT SYARIAH DI DAERAH ISTIMEWA YOGYAKARTA: (Studi Pada Bank Perkreditan Rakyat Syariah Yang Terdaftar di Otoritas Jasa Keuangan Tahun 2015-2018) - Rinda Tungga Dewi; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
Statistical data on financial services authority in 2015-2018 for the financial ratios of sharia commercial banks and sharia business units fluctuated, where an increase and decrease from year to year had a bad impact on the finance of Islamic banks. Insufficient capital along with an increased level of Non Performing Financing (NPF) can result in a decrease in the level of profitability. This study aims to examine the factors that affect the profitability of Islamic people credit banks in Yogyakarta. This approach uses descriptive quantitative, with a sample of 143 data obtained from the quarterly financial statements of the Financial Services Authority for the 2015-2018 period, the hypothesis test uses multiple regression tests using the SPSS 21 program. The results of this study indicate that capital variables influence profitability, liquidity variables affect profitability, Non Performing Financing (NPF) variables affect profitability, inflation variables affect profitability, and capital, liquidity, NPF and inflation variables together influence profitability.